The Criminal Act of Child Molestery on The Based on Mutual Consent in Qanun Jinayat is Reviewed with the Principle of Legal Preference (Decision No. 6/Jn/2019/Ms.Aceh) - Muhammad Akmal TaufiqulHakim; Emmilia Rusdiana (Universitas Negeri Surabaya, 2025)
Criminal acts in Aceh are regulated in Qanun Number 6 of 2014 concerning Jinayat, which is a regional regulation at the provincial level based on Islamic law. In the case of indecent acts committed against children on the basis of mutual consent in Decision No. 6/JN/2019/MS. Aceh acquitted the defendant based on Article 1 number 27 of Qanun Number 6 of 2014 concerning Jinayat. The purpose of this study is to examine indecent acts against children in Qanun No. 6 of 2014 concerning Jianayat using the principle of preference lex superiori derogat legi inferiori and lex specialist derogat legi generali. This study is normative and uses a case and statutory approach as a research methodology. The results obtained from this study are that there was an error by the judge in acquitting the defendant, based on Law No. 35 of 2014 concerning Child Protection and the Criminal Code which is based on the principles of lex superiori derogat legi inferiori and lex specialist derogat legi generali states that a child's consent cannot be used as a reason to exempt a person from the crime of molestation of a child based on mutual consent.